The Relationship between Placement, Environment, and Work Motivation with Employee Performance at the Medan City Education and Culture Office - Kamarullah, Reza; Rijal, Muhammad; Rinaldi, Rinaldi; Rifyal, Rifyal; Muhibuddin, Muhibuddin; Safrida, Safrida (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to analyze the influence of job placement, work environment, and work motivation on employee performance at the Medan City Education and Culture Office. The research method used was quantitative with a survey approach through a questionnaire to 109 respondents. The results of the study show that all three variables, both individually and simultaneously, have a positive and significant influence on employee performance. Work motivation has the most dominant influence, followed by the work environment and work placement. This research supports the theory of Person-Job Fit and Self-Determination and provides recommendations to improve employee performance through appropriate placement, a conducive work environment, and effective motivation.